Feasibility Study on an Advanced Layered Haircut Tutorial Video for the Beauty Therapy Program - Septia Ayu Imelda; Sri Endah Wahyuningsih (Universitas Negeri Semarang, 2026)
This study aims to enrich teaching materials by presenting educational videos on advanced layer cut techniques and toevaluate their effectiveness as a learning tool. The research method used is Research and Development (R&D), adopting the ADDIE development model, which includes the phases of needs analysis, design, product development, implementation, and evaluation. Data collection was conducted using validation instruments completed by subject matter experts and media experts, as well as a questionnaire to gather user feedback. The findings of this study indicate that the developed video media was deemed suitable based on assessments by subject matter experts, media experts, and user responses. Furthermore, this instructional video successfully presented the steps for layered hair cutting in a structured, engaging, and easy-to-understand manner, thereby facilitating learners in mastering and practicing the layered hair cutting method.